2022
DOI: 10.3389/fmicb.2022.989421
|View full text |Cite
|
Sign up to set email alerts
|

Mouse feeding study and microbiome analysis of sourdough bread for evaluation of its health effects

Abstract: Sourdough bread fermented with yeast and lactic acid bacteria (LAB) is thought to have various beneficial health effects. However, its beneficial effects were not fully evaluated with in vivo mouse model. To evaluate these effects in vivo, a mouse feeding study and microbiome analysis of white bread containing 40% sourdough (WBS) and yeast-leavened white bread (WB) were performed. Although feed consumption and body weight increased with WBS, the glycemic index was reduced, suggesting a diabetes-lowering effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…During sourdough fermentation, the dough is acidified to a pH less than 5.0, which solubilizes phytate salts of Fe 2+ , Mg 2+ and Ca 2+ while maintaining the activity of cereal phytases close to their optima ( 205–208 ). Improved bioacessibility after sourdough fermentation was confirmed by in vitro experiments ( 209 ). Consumption of sourdough bread increased mineral absorption in rats when compared to a diet based on yeast-fermented bread ( 210 ).…”
Section: Reduction Of Anti-nutritive Compounds and Contaminantsmentioning
confidence: 86%
“…During sourdough fermentation, the dough is acidified to a pH less than 5.0, which solubilizes phytate salts of Fe 2+ , Mg 2+ and Ca 2+ while maintaining the activity of cereal phytases close to their optima ( 205–208 ). Improved bioacessibility after sourdough fermentation was confirmed by in vitro experiments ( 209 ). Consumption of sourdough bread increased mineral absorption in rats when compared to a diet based on yeast-fermented bread ( 210 ).…”
Section: Reduction Of Anti-nutritive Compounds and Contaminantsmentioning
confidence: 86%
“…The existence of a gut–lung axis and the relationship between asthma and gut microbiota has already been reported [ 41 , 42 ]. Previous studies demonstrated that probiotics or sourdough can change the gut microbiota in humans and mice [ [43] , [44] , [45] , [46] , [47] ]. Thus, the administration of bread fermented with S. cerevisiae UFMG A-905 could have altered mice gut microbiota and, consequently, prevented asthma development.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al [112] Yeast-leavened white bread and sourdough bread, male C57BL/6 mice Mice fed with sourdough bread showed a diabeteslowering effect by decreasing the GI, owing to the existence of dietary fiber and SCFAs. Some useful bowel bacteria like Akkermansia, Bifidobacterium, and Lactobacillus were increased in mice in the sourdough bread-fed group.…”
Section: Sourdough Fermentation and Gut Microbiotamentioning
confidence: 99%